Effects of various training modalities on blood volume - Schmidt, W.; Prommer, N. (Scandinavian Journal of Medicine & Science in Sports, 2008)
It is controversially discussed whether soccer games should be played at moderate (2001-3000 m) and high altitudes (3001-5500 m) or should be restricted to near sea level and low altitude (501-2000 m) conditions. Athletes living at altitude are assumed to have a performance advantage compared with lowlanders. One advantage of altitude adaptation concerns the expansion of total hemoglobin mass (tHb-mass), which is strongly related to endurance performance at sea level. Cross-sectional studies show that elite athletes posses ~35% higher tHb-mass than the normal population, which is further elevated by 14% in athletes native to altitude of 2600 m. Although the impact of this huge tHb-mass expansion on performance is not yet investigated for altitude conditions, lowland athletes seek for possibilities to increase tHb-mass to similar levels. At sea level tHb-mass is only moderately influenced by training and depends more on genetic predisposition. Altitude training in contrast, using either the conventional altitude training or the live high-train low (>14 h/day in hypoxia) protocol for 3-4 weeks above 2500 m leads to mean increases in tHb-mass of 6.5%. This increase is, however, not sufficient to close the gap in tHb-mass to elite athletes native to altitude, which may be in advantage when tHb-mass has the same strong influence on aerobic performance at altitude as it has on sea level.